Association between bipolar spectrum disorder and bone health: a meta-analysis and systematic review protocol. Issue 2 (28th February 2017) - Chandrasekaran, Vinoomika; Brennan-Olsen, Sharon L; Stuart, Amanda L; Pasco, Julie A; Berk, Michael; Hodge, Jason M; Williams, Lana J
Abstract : Introduction: Bipolar spectrum disorder is a chronic, episodic illness, associated with significant personal, social and economic burden. It is estimated to affect ∼2.4% of the population worldwide and is commonly associated with psychological and/or physiological comorbidities. Osteoporosis is one such comorbidity, a disease of bone that is asymptomatic until a fracture occurs. This systematic review attempts to capture, collate, assess and discuss the literature investigating the association between bipolar spectrum disorder and bone health. Methods and analysis: We aim to identify articles that investigate the association between bipolar spectrum disorder and bone health in adults by systematically searching the MEDLINE, PubMed, OVID and CINAHL databases. Two independent reviewers will determine eligibility of studies according to predetermined criteria, and methodological quality will be assessed using a previously published scoring system. A meta-analysis will be conducted, and statistical methods will be used to identify and control for heterogeneity, if possible. If numerical syntheses are prevented due to statistical heterogeneity, a best evidence synthesis will be conducted to assess the level of evidence for associations between bipolar spectrum disorder and bone health. Ethics and dissemination: Ethical permission will not be required for this systematic review since only published data will be used. This protocol will be registered with PROSPERO. Findings of the review will be published in a peer-reviewed scientific journal, and will be presented to clinical and population health audiences at national and international conferences.